Genetic regulatory axis between AGR2 and ESR1 promotes breast cancer progression - M. Aiman Mohtar; Delphine Fessart; Chia Yuh Cai; Syazalina Zahari; Saiful Effendi Syafruddin; Muhammad-Redha Abdullah-Zawawi; Valerie Le Morvan; Said Taouji; Ted Hupp (PLoS ONE, 2026)
Anterior gradient protein 2 (AGR2), a member of the protein disulfide isomerase family, plays a critical role in endoplasmic reticulum proteostasis and has been implicated in breast cancer progression. However, the downstream regulatory programs and signaling pathways governed by AGR2 remain incompletely defined. Here, we employed CRISPR–Cas9-mediated knockout of AGR2 in breast cancer cells to systematically investigate the functional and transcriptional consequences of AGR2 loss. AGR2 depletion resulted in significant suppression of cell migration, invasion, and chemoresistance. Unbiased transcriptomic profiling by RNA sequencing revealed extensive differential gene expression, implicating AGR2 in receptor-mediated signaling, oxidative stress responses, and cell adhesion pathways. Protein–protein interaction network analysis identified several highly connected hub genes within the AGR2-regulated transcriptome, including estrogen receptor alpha (ESR1/ERα), cadherin 1 (CDH1), androgen receptor (AR), lymphocyte cell-specific protein-tyrosine kinase (LCK), S100 calcium binding protein P (S100P), parkin RBR E3 ubiquitin ligase (PRKN), and decay-accelerating factor (CD55). Notably, ERα emerged as a prominent node within this network, consistent with prior reports linking ERα and AGR2 biology. Integration with publicly available epigenomic datasets further supports a potential regulatory connection between ERα-associated chromatin landscapes and AGR2 expression. Together, these findings define AGR2-dependent transcriptional networks in breast cancer and identify ESR1-associated signaling as a key pathway perturbed upon AGR2 loss, providing a foundation for future mechanistic studies targeting this regulatory interaction.